2017
DOI: 10.3390/ijms18061210
|View full text |Cite
|
Sign up to set email alerts
|

Association of Smoking, Alcohol Use, and Betel Quid Chewing with Epigenetic Aberrations in Cancers

Abstract: Numerous environmental factors such as diet, alcohol use, stress, and environmental chemicals are known to elicit epigenetic changes, leading to increased rates of cancers and other diseases. The incidence of head and neck cancer, one of the most common cancers in Taiwanese males, is increasing: oral cancer and nasopharyngeal carcinoma are ranked fourth and tenth respectively, among the top ten cancers in this group, and a major cause of cancer-related deaths in Taiwanese males. Previous studies have identifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
38
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 126 publications
0
38
0
Order By: Relevance
“…While the acquired genetic factors cannot be controlled in their early steps of mutation accumulation, environmental exposure can significantly affect the pathogenesis and the prognosis of these patients [ 8 , 9 ]. The major environmental components are tobacco smoking, betel quid chewing, alcohol consumption, and poor oral hygiene and infections, alongside other specific dietary habits or specific pollutant exposure [ 6 , 7 , 10 , 11 ]. The totality of risk factors are integrated into the exposome [ 12 ], this being an important step in the evaluation of internal and external exposure, generally related to the co-occurrence of multiple toxic environmental agents [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…While the acquired genetic factors cannot be controlled in their early steps of mutation accumulation, environmental exposure can significantly affect the pathogenesis and the prognosis of these patients [ 8 , 9 ]. The major environmental components are tobacco smoking, betel quid chewing, alcohol consumption, and poor oral hygiene and infections, alongside other specific dietary habits or specific pollutant exposure [ 6 , 7 , 10 , 11 ]. The totality of risk factors are integrated into the exposome [ 12 ], this being an important step in the evaluation of internal and external exposure, generally related to the co-occurrence of multiple toxic environmental agents [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, high expression of circ_0000199 was associated with betel quid chewing, tumor size, and lymph node metastasis, suggesting its potential clinical application as an independent factor for predicting survival and disease recurrence of OSCC patients. The epidemiological studies have showed that betel quid chewing is closely related to the occurrence of OSCC 23 . In 2003, the World Health Organization identified betel nut as a primary carcinogen.…”
Section: Discussionmentioning
confidence: 99%
“…Cigarette smoking and alcohol consumptions are other risk factors for oral cancer [32]. Those habits also cause alteration of DNA methylation [33,34]. In fact, previous studies demonstrate clear evidence that development of oral cancer follows the same biological pathways irrespective of the source of carcinogenic exposure [35,36].…”
Section: Discussionmentioning
confidence: 99%